1998
DOI: 10.1097/00001756-199806220-00043
|View full text |Cite
|
Sign up to set email alerts
|

Hand motor cortical area reorganization in stroke

Abstract: The anatomical and functional correlates of the hand sensorimotor areas was investigated in a stroke patient with a malacic lesion in the left fronto-parieto-temporal cortex. The patient presented hemiplegia and motor aphasia 12 months earlier, followed by an excellent motor recovery. Transcranial magnetic stimulation mapping, functional magnetic resonance and magnetoencephalography were used as methods of functional imaging and all yielded consistent results. In particular, an asymmetrical enlargement and pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
86
2

Year Published

2000
2000
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(93 citation statements)
references
References 4 publications
5
86
2
Order By: Relevance
“…There is some evidence that such changes may occur after stroke as well. 16,17 The notion that local changes in the primary SMC may contribute to recovery is consistent with studies of motor learning in humans. For example, the work of Karni et al 18 has shown that with improved performance on a complex motor task, there is an expansion of the representation for finger movements in the primary SMC.…”
supporting
confidence: 69%
See 1 more Smart Citation
“…There is some evidence that such changes may occur after stroke as well. 16,17 The notion that local changes in the primary SMC may contribute to recovery is consistent with studies of motor learning in humans. For example, the work of Karni et al 18 has shown that with improved performance on a complex motor task, there is an expansion of the representation for finger movements in the primary SMC.…”
supporting
confidence: 69%
“…14,15 Preliminary data from a few patients have suggested that this might also occur in stroke. 16,17 There did not appear to be a relationship between the degree of functional deficit and the extent of the posterior shift in the geometric center of the SMC activation cluster, Figure 3. Anterior-posterior values (y-axis) of geometric centers of activation clusters in the contralateral primary SMC for individual patients (squares) performing sequential (A) and hand-tapping (B) tasks, given in Talairach coordinates.…”
Section: Discussionmentioning
confidence: 92%
“…First weakened body part. With recovery following stroke, demonstrated to be valuable in a rat model, there are now Rossini and co-workers [11,56,61] have demonstrated several clinical trials showing that amphetamine given enlarged and / or relocated TMS maps of the recovering together with physical therapy is better than physical muscles, indicating the probable importance of contralatertherapy alone [17,64]. The mechanism for this drug action al hemisphere plasticity mechanisms in recovery.…”
Section: Mechanisms Of Plasticitymentioning
confidence: 99%
“…Although less effectively than in children (Müller et al, 1999), reorganization may also occur later in life. This may occur into ipsilateral cortex (Lazar et al, 1997;Rossini et al, 1998). When sufficient damage has occurred (Kertesz, Lau, & Polk, 1993), the contralateral hemisphere has also been shown to play a role in recovery from aphasia in adults (Thomas et al, 1997;Karbe et al, 1998;Thulborn et al, 1999).…”
Section: Introductionmentioning
confidence: 99%